Pengaruh Transformasi Digital dan Bisnis Online Terhadap Pola Perilaku Masyarakat Ciputat Timur - Adawiyah, Rabiatul (Jurnal Riset Bisnis dan Investasi, 2023)
Digital transformation and convenience in online shopping activities have led to changes in people's behavior patterns, especially during the Covid-19 pandemic. Therefore, this research was conducted to obtain information about the influence of digital transformation and online business on people's behavior patterns. This research is quantitative research with a survey method conducted in East Ciputat. For the research conclusions to apply to the entire community of East Ciputat, a survey method was used using path analysis techniques in hypothesis testing. A total of 60 people were selected as samples through the calculation of the Slovin Formula. Based on the results of the calculation of research data and the results of data analysis, it can be concluded that digital transformation has a direct positive effect on behavioral patterns, online business has a direct positive effect on behavioral patterns, and digital transformation has a direct positive effect on online business.